Enhanced Anti-Obesity Activities of Red Mold Dioscorea When Fermented Using Deep Ocean Water as the Culture Water - Tzu-Ming Pan; Chun-Lin Lee; Jyh-Jye Wang; Tsung-Yu Tsai; Bai-Luh Wei; Yi-Hsin Kung; Tzu-Ying Lung; Li-Chun Wang (Marine Drugs, 2013)
Deep ocean water (DOW) has, in previous studies, been found to be a novel anti-obesity drink and useful in raising Monascus-produced monascin and ankaflavin levels. This may resolve the limited anti-obesity ability of red mold dioscorea (RMD) known as the Monascus purpureus-fermented Disocorea batatas. This study aims to compare the anti-obesity effect of DOW-cultured RMD (DOW-RMD) and ultra-pure water-cultured RMD (UPW-RMD) in rats fed on a high fat diet. Moreover, the effect of ions composition of DOW and DOW-influenced functional metabolites change of RMD on the differentiation and lipogenesis regulation were investigated using 3T3-L1 pre-adipocytes. In the animal test, compared to UPW-RMD, DOW-RMD possessed better ability to inhibit increases in weight gain, and better feed efficiency, body-fat pad and cross-sectional area of adipocytes. In the cell test, the anti-obesity abilities of DOW-RMD in inhibiting PPARγ and C/EBPα expression in differentiation and lipoprotein lipase activity in lipogenesis were contributed to by the DOW-increased monascin and ankaflavin levels and the ions of DOW, respectively.